(untitled) (Journal of Asian Development Studies, 2024)
Translation is the ability to convey information from one language to another with the ability to meet the linguistic and cultural specifics of the target language. The effect of this approach on the translation of cultural references and emotional connotations in the selected poems of Noshi Gillani has also been examined in this study. The principle of dynamic is used to translate the meaning and receiving impact of the source text for the target audience in the target language However, translating the Urdu poetry to English is not possible without problems such as conveying cultural symbols, idioms, and emotions. Translation has a significant role in bridging linguistic and cultural gaps that allow readers to appreciate the literary works of different writers. Employing the qualitative research strategy, the study provides a detailed breakdown, analysis and discussion of the selected poems in both the Urdu version and the English translation. The theoretical underpinnings have their foundation in Eugene Nida’s theory of dynamic equivalence together with the advantages and disadvantages of the theory. The study shows that, although a dynamic approach preserves the transfer of meaning and readability, it sacrifices cultural and emotional context that is innate to Pakistani Urdu poetry. The paper finds that while translating, the translators of the future should compromise on the equivalents of meaning with the originality of the cultural and poetic figures; therefore, the cooperation of linguists with speakers of the poetic word should be encouraged and valued.